Pengaruh Pendidikan Kesehatan tentang Stimulasi Perkembangan Anak Usia 0-3 Tahun terhadap Pengetahuan dan Sikap Orang Tua - Bagustin Yopy Fatimah Nurwegha; Bisepta Prayogi (STIKes Patria Husada Blitar, 2014)
Introduction: Human development is the perfect growing of functioning tool that can be passed through the body to grow, mature, and learn. The first 3 years is the important step towards an adult in a child's life. Parents must provide appropriate stimulation to the child's age, therefore parents should have a good knowledge and attitude. The purpose of this study is to analyzed stimulatory effect of health education on the development of children aged 0-3 years knowledge and attitudes towards parents. Method: Research design was one group pre - test and post-test design.Research sample was 35 parets at Posyandu Matahari, Plosorejo Village, Blitar District of Kademangan at May 7th to 14th, 2012, its choosed with purposive sampling. The data was collected using questionnaire. AnalysisÂ using the Wilcoxon Signed Rank Test with significance Î± = 0.005. Results: The result showed enough knowledge on pre-test (67,7) and post-test was good (83.5), while the attitude on the pre-test was good (70.1) and post-test was excellent (86.5) with the level of significance p = 0.001 on knowledge and attitudes. Discussion: Knowledge and attitudes of the respondents affected increased to better health education. The role of the nurse as an educator in the health service needs to be improved in order to improve knowledge and attitudes.